Poesía femenina universitaria 1985. - Suárez, Ramón (Revista Chilena de Humanidades, 2016)
Prof. Suárez examines a section of the poetical work of a group of sh1dents adscribed to the Program of Licentiatura en Litera tura of the Faculty of Philosophy, Humanities and Education of the University of Chile, namely, Mónica de Simone, Nira Reyes, Marcela Toro and Patricia Mardones. His comments represent a valuable help in approaching the creative work of these women poets.